ASSESSING THE ROLE OF ISLAMIC BANKING IN DRIVING INDONESIA’S ECONOMIC GROWTH DURING COVID-19 - Anisa, Vera Novia; Indri Supriani; Yunice Karina Tumewang (Bank Indonesia, 2025)
This study examines the role of Islamic banking in supporting Indonesia’s economic growth during the unprecedented disruption caused by the COVID-19 pandemic from March 2020 to May 2023. The study employs the Autoregressive Distributed Lag (ARDL) model to investigate the relationship between key Islamic banking indicators and economic performance, as proxied by the Industrial Production Index (IPI), in both the short and long term. The empirical findings suggest that Islamic bank financing, as measured by the financing-to-deposit ratio (FDR), gross fixed capital formation (GFCF), and total assets, has a significantly positive impact on long-term economic growth. However, its short-term effects were relatively limited. These results underscore the importance of strengthening regulatory frameworks and promoting profit-and-loss-sharing mechanisms to enhance the resilience and developmental impact of Islamic banking, particularly in supporting economic recovery following financial shocks. By focusing on a crisis, this study offers novel empirical insights into the stabilizing role of Islamic banking during periods of economic turbulence and contributes to promoting economic resilience.